Exploring the management practices of an owner-manager small business Matsarawak Travel And Tours Services Sdn. Bhd. / Abdul Jalil Lob ... [et al.] - Kamri, Thalany; Mohd. Sahari, Rosmawati; Jamain, Mohd. Sapawi; Gaik, Mary; Lob, Abdul Jalil (2003)
MatSarawak Travel and Tours Services Sdn. Bhd. is an owner/manager small business company recognized as providing the cheapest Umrah and Umrah & Ziarah packages available in Sarawak. Presently, there are signs that it is facing difficulty in managing its Umrah and Umrah & Ziarah packages. This project examines the business and management problems currently faced by the Company and to offer solutions and recommendations to the Company. The study involves examination of the management processes directly related to the problem faced by the Company through examination of the company’s cash-flow management, costing of its products, its cost volume profit analysis. A management audit of the Company’s management practice and the Internal Factor Evaluation is conducted to determine its internal strength and weakness. A survey of some of the Company’s customers in Kuching is undertaken to measure the level of customer satisfaction with regards to the service provided. The findings showed that despite having positive cash flow the Company lacked funds to send its customers as promised. The cause can be attributed to poor pricing of products as well as poor product mix and weaknesses in management. This study proves that a good business idea, and customer focus cannot ensure a thriving business if there is absence of leadership and basic business skills.